PENGEMBANGAN MODUL KALKULUS II MENGGUNAKAN MODEL KOOPERATIF TIPE JIGSAW BERBASIS INQUIRI - Yuntawati, Yuntawati; Aziz, Lalu Abdul (Jurnal Ilmiah IKIP Mataram, 2018)
The purpose of this development is to produce the product of calculus II module. This developed module is expected to be useful for lecturers and students as a source of more information in learning. This research is a research developing module using cooperative model of Jigsaw type based inquiry. Data collection techniques in this study using observation sheets, interview guides and test sheets. The data obtained are qualitative and quantitative data. The results of this study indicate the instructional materials in the form of calculus II modules developed included in the effective criteria, in terms of lecturer's ability to manage learning using the average module 3.47 with high criteria, student and lecturer activities obtained the ideal achievement of student activities and lecturers fulfilled from Limit of percentage of ideal time of activity of student and lecturer, and final test obtained 78% of student get score more than 6 after they follow learning using cooperative model of jigsaw type based inquiry with developed module